Pneumatosis Cystoides Intestinalis: A rare cause of intestinal obstruction (KYAMC Journal, 2022)
There are many well-known causes of acute or sub-acute intestinal obstruction. But Pneumatosis cystoides intestinalis (PCI) is a rare cause and can easily be misdiagnosed. PCI refers to presence of air within the wall of small or large intestine. This benign disease having both idiopathic and secondary causes with different contributing pathogenic factors that confuses many doctors. In most of the time it is asymptomatic, but clinical signs and imaging impressions may mimic true abdominal visceral perforation or soft tissue stranding leads to mechanical obstruction. PCI is sometimes incidentally found during radiological evaluation, endoscopic procedure or laparotomy. Surgery is not recommended for PCI if there was no intestinal obstruction, because of high operative risk. So correct diagnosis is imperative as treatment of PCI is generally conservative. We are presenting a case of intestinal obstruction who underwent to laparotomy followed by the histopathological diagnosis as a case of PCI. KYAMC Journal Vol. 13, No. 03, October 2022: 177-180